(untitled) (Architecture Image Studies, 2025)
Although extensive theoretical discussions examine how interior atmospheres are constructed in cinema, particularly how lighting and illumination guide viewer perception, comprehensive empirical studies that explore how these atmospheric elements are understood and conceptualized by design students across different film genres remain limited. Addressing this gap, the present study investigates how 102 students enrolled in the Form Light Color course in the Interior Architecture Department at Istanbul Aydın University systematically analyzed interior scenes from five film genres: horror and thriller, romance, comedy, fantasy, and science fiction, focusing specifically on lighting and illumination. The research employs a multi stage methodological framework consisting of data collection, qualitative coding, thematic content analysis using MAXQDA, word cloud modelling, and artificial intelligence based visual generation through the GEMINI system. The findings reveal distinct patterns of light and atmosphere for each genre. Horror and thriller films rely on low key and shadow intensive lighting. Romance films emphasize warm and diffused illumination. Comedy films frequently use bright and evenly distributed lighting. Fantasy films highlight colorful, magical, and multidirectional illumination. Science fiction films are characterized by neon based, cold, and technologically structured lighting schemes. By bringing together student perception, qualitative analysis, and artificial intelligence supported visual modelling, this study offers a novel methodological contribution to both film studies and design education literature. The findings provide a deeper understanding of how cinematic lighting and atmosphere are constructed, interpreted, and visually represented.